2016
DOI: 10.1111/jcpe.12634
|View full text |Cite
|
Sign up to set email alerts
|

Does obesity influence the subgingival microbiota composition in periodontal health and disease?

Abstract: Obesity is associated with increased levels and proportions of periodontal pathogens, especially in patients with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 16 publications
8
76
2
2
Order By: Relevance
“…The finding of the present study states that the PD levels were higher in group 2 and group 3 patients. In a recent study by Maciel and colleagues, it was concluded that obese patients with deep PDs harbored higher levels of periodontopathogenic bacteria as compared to nonobese individuals. Although the cause of this association is still unknown, it is speculated that obesity‐associated immune changes in periodontal tissues alter the pocket environment and/or host defenses, affecting the subgingival microbial colonization .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of the present study states that the PD levels were higher in group 2 and group 3 patients. In a recent study by Maciel and colleagues, it was concluded that obese patients with deep PDs harbored higher levels of periodontopathogenic bacteria as compared to nonobese individuals. Although the cause of this association is still unknown, it is speculated that obesity‐associated immune changes in periodontal tissues alter the pocket environment and/or host defenses, affecting the subgingival microbial colonization .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Maciel and colleagues, it was concluded that obese patients with deep PDs harbored higher levels of periodontopathogenic bacteria as compared to nonobese individuals. Although the cause of this association is still unknown, it is speculated that obesity‐associated immune changes in periodontal tissues alter the pocket environment and/or host defenses, affecting the subgingival microbial colonization . Further studies assessing the microbiological and immune‐inflammatory aspect of peri‐implant sites in obese patients are recommended to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen from Table 1 that only 36% of obese patients brushed twice daily as compared to 73% non-obese. 17,23 In a recent study by Maciel et al 17 Recent investigations have confirmed that obese patients are more susceptible to periodontal attachment loss with increased alveolar bone destruction and is associated with poor periodontal therapy response due to systemic inflammation. 22 Moreover, higher peri-implant destruction in obesity may be described by the increased prevalence of certain periopathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although PD in obese group was higher as compared to nonobese, these differences did not show statistical difference and these pockets cannot be considered pathological as the scores were < 4 mm. It is suggested that overweight patients with higher and deep PD harbor enhanced percentage levels of bacteria causing periodontal diseases . Although the direct cause‐effect of this link needs validation, it is contemplated that obesity‐associated immune changes in peri‐implant structures may alter the pocket environment and/or host defenses, affecting the subgingival bacterial niche around dental implants.…”
Section: Discussionmentioning
confidence: 99%